Real-world data analysis for factors influencing the quality check status in FoundationOne CDx cancer genomic profiling tests - Hiroaki Niitsu; Hikaru Nakahara; Katsunari Ishida; Yoshie Kaneko; C. Nelson Hayes; Koji Arihiro; Takao Hinoi (Scientific Reports, 2025)
Abstract Comprehensive genomic profiling (CGP) testing is used worldwide for personalized cancer treatment. Unstained slides from formalin-fixed paraffin-embedded (FFPE) blocks are required for tissue-based CGP testing. However, the use of low quality FFPE specimens can result in testing failure or invalid results. Although several previous studies have indicated that the quality of genomic testing is affected by various factors, the factor(s) that has the greatest influence on CGP testing has not been well studied in real-world data. Thus, we conducted a large-scale multi-institutional study in Hiroshima, Japan to investigate the factors associated with quality check status in FoundationOne CDx CGP testing using real-world data from 1,204 participants from an area with a population of approximately 2.7 million. This study revealed low percentage of tumor nuclei in FFPE specimen, long-term storage of FFPE block, and pancreatic cancer as independent risk factors for qualified status. Of the three factors, percentage of tumor nuclei had the largest effect on quality check status, while the magnitudes of the effects of storage time of FFPE or pancreatic cancer were minor. Collectively, our real-world data indicate that tumor purity is the most important factor for successful CGP, and we would suggest greater than 35% as an ideal percentage of tumor nuclei for CGP submission.